Sanitasi Terminal pada Era New Normal : Studi Kasus Terminal Tipe A Simbuang Mamuju - Fahrul Islam; Agus Erwin Ashari; Haeranah Ahmad (Jurnal Sehat Mandiri, 2022)
Poor access to sanitation is one of the causes of disease in public places including at bus station. This research uses observational methods with a descriptive approach. The purpose of this study was to determine the sanitary condition of Simbuang Mamuju Type A Station. The object of this study is The Environmental Sanitation Facility of the Simbuang Type A Station, Mamuju Regency. The instrument used is an assessment instrument for environmental health examination of public transportation infrastructure by the Health Human Resources Education Center in 2018. The results showed that the condition of the clean water supply facilities was qualified with a percentage of the total score of 70%, but there were still components that did not meet the requirements, namely the components of periodic clean water quality inspection in the lab. Toilet conditions are not eligible with a percentage of the total score below 70%, which is 65%. unqualified components are toilets that are not clean and smelly. The condition of the waste disposal facility is qualified with a percentage of the total score of 87.5%, but there are still components that do not meet the requirements, namely the waste component is disposed of / transported > every 3 days. Conclusion: The Sanitation Condition of the Simbuang Type A Station is not healthy yet. Suggestion: all components that are not qualified to be paid more attention to.